Hard Times in America's Laboratory for Democracy: Wisconsin Legislative Politics 1966 and Now - Stampen, Jacob O. (My University, 2007)
As a higher education policy analyst at the National Center for Higher Education, Jacob Stampen learned that the health of political systems greatly influence the quality of higher education. However, as a teacher and scholar, he noticed the research literature lacks sufficient methods for depicting the differences between healthy and unhealthy systems. To fill this gap, Stampen has devised a way to graphically display changes in the behavior of political systems. In this presentation, he will illustrate the seldom-noticed differences in the voting behavior of two Wisconsin Legislatures, one of which he argues is healthy and the other unhealthy. He will also discuss the implications of these differences for higher education in Wisconsin and what universities can do to improve the health of the state's political system. Stampen's article on the same topic, "Rise of Block Voting in the Wisconsin State Legislature One Reason for Public Policy Lull," appeared on WisOpinion.com on August 7, 2007.
Keywords: Accountability, Autonomy, and Politics